Impact of Neoliberalism on Language Educational Policies - Karki, Tek Mani (Panauti Journal, 2024)
This article scrutinizes the pervasive influence of neoliberalism on education, language education policies, and language of instruction. Employing a content analysis design informed by established principles of qualitative research, the study explores the juncture of neoliberal ideologies with educational practices. Neoliberalism’s emphasis on deregulation, privatization, and market-driven approaches shapes educational systems globally, with reflective implications for language education. Scholars note the transformation of education into a commodity, driven by the prioritization of economic growth and individual competitiveness. Within this framework, English proficiency emerges as a key determinant of access to economic opportunities, leading to the proliferation of English language teaching institutions. Moreover, neoliberal policies influence language of instruction decisions, with governments adopting market-oriented strategies such as English medium instruction. The article underscores the need for critical examination of neoliberalism’s impact on education, highlighting the tensions between market-driven principles and educational equity. By elucidating the complexities of neoliberalism’s effects on language education, the study contributes to a nuanced understanding of contemporary educational practices and calls for the preservation of inclusive and accessible education for all.